The biological functions of proanthocyanidin and its application in pig production - Yu, Aiying; Sun, Lingli; Chen, Lian; Wang, Dan; Li, Zhiyi; Wang, Yuan; Wang, Zhenjiang; Lin, Sen (Frontiers in Veterinary Science, 2025)
Proanthocyanidins (PACs) are natural polyphenolic compounds widely distributed in various plants, which are mixtures of oligomers and polymers formed by the polymerization of different numbers of catechins and epicatechins. PACs exhibit a range of biological activities, including antioxidant, anti-inflammatory, anti-cancer, anti-atherosclerotic, hypoglycemic, and antihypertensive effects, as well as the ability to regulate intestinal flora and promote fat metabolism. These properties render PACs highly promising for applications in the food, pharmaceutical, and cosmetic industries, garnering substantial interest from researchers globally. Additionally, PACs demonstrate significant nutritional benefits in animal husbandry. Dietary PACs can enhance animal growth, mitigate oxidative stress, decrease feeding expenses, and offer an environmentally friendly, antibiotic-free alternative. Therefore, PACs have great application potential in the field of pig production. This article reviews the basic properties, biological functions, and research status and application in pig production of PACs, aiming to provide theoretical guidance for the development of substitute antibiotic feed additives.